Field experience of remote monitored and controlled CP systems. (June 2015) - Atkins, C.; Brueckner, R.; Lambert, P.; Bennett, M.
Abstract: In 1993 the first of a series of cathodic protection (CP) systems were installed on the approach viaducts of a major UK bridge structure. Over subsequent years the structure had additional phases of repairs and CP installations. Due to the requirement to competitively tender each phase, a range of CP systems were installed between 1993 and 2013. The final phase was to replace the various power, control and monitoring systems that had been installed with a smaller number of more up to date units. As part of this process the historic operating performance of each system was employed to optimize the number and size of zones and the number of monitoring probes. In addition, a number of systems were installed but not energized until the final phase had been completed. This paper presents a review of the performance of the systems and the associated control equipment over the twenty year period.